Anabolic-androgenic steroids are linked to depression and anxiety in male bodybuilders: the hidden psychogenic side of anabolic androgenic steroids - Baris Karagun; Selin Altug (Annals of Medicine, 2024)
AbstractBackground The prevalence of anabolic-androgenic steroids (AAS) use is on the rise among athletes and bodybuilders worldwide. In addition to the well-documented adverse effects on hepatic, renal, and reproductive functions, there is an increasing recognition of psychiatric complications associated with AAS use. This study aimed to investigate psychiatric morbidity among male bodybuilders who are AAS users.Methods In this cross-sectional study, 25 male bodybuilders using AAS (mean age 31.2 ± 8.9 years) were compared with a control group of 25 healthy male bodybuilders matched in age (31.3 ± 5.5 years). The demographic, hormonal, and biochemical parameters of the participants were recorded. The impact of AAS use on psychiatric morbidity was assessed using the Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI) in both groups.Results The BDI and BAI scores were significantly higher in male bodybuilders using anabolic-androgenic steroids (p < 0.0001). While the control group showed no instances of anxiety, seven individuals in the AAS user group reported mild anxiety. No participants in the control group exhibited depression, whereas seven AAS users displayed depressive symptoms (4 mild, 3 moderate). Correlations were observed between lactate dehydrogenase (LDH) levels and BAI scores, creatinine levels and both BAI and BDI scores, as well as between estradiol levels and BDI.Conclusion The study concluded that AAS use among male bodybuilders is associated with elevated levels of depression and anxiety. Our findings suggest a potential correlation between anxiety and depression levels and the levels of creatinine, LDH, and estradiol in AAS users.